Economic evaluation of individualized nutritional support in medical inpatients: Secondary analysis of the EFFORT trial. Issue 11 (November 2020) - Schuetz, Philipp; Sulo, Suela; Walzer, Stefan; Vollmer, Lutz; Stanga, Zeno; Gomes, Filomena; Rueda, Ricardo; Mueller, Beat; Partridge, Jamie; ,
Summary: Background & aims: Existing guidelines support the importance of nutritional interventions for medical inpatients at malnutrition risk to alleviate the impact of malnutrition on outcomes. While recent studies have reported positive effects of nutritional support on health outcomes, limited evidence exists on whether in-hospital nutritional support also results in economic advantages. We report the results of the economic evaluation of EFFORT—a pragmatic, investigator-initiated, open-label, multicenter trial. Methods: A total of 2028 medical inpatients at nutritional risk were randomly assigned to receive individualized nutritional support to reach protein and energy goals (intervention group; n = 1015) or standard hospital food (control group; n = 1013). To calculate the economic impact of nutritional support, a Markov model was developed with relevant health states. Costs were estimated for days in normal hospital ward and in the Intensive Care Unit (ICU), hospital-acquired complications, and nutritional support. We used a Euro conversion rate of 0.93216 Euro for 1 Swiss Franc (CHF). Results: The estimated per-patient cost was CHF90 (83.78 €) for the in-hospital nutritional support and CHF283.85 (264.23 €) when also considering dietitian consultation time. Overall costs of care within 30 days of admission averaged CHF29, 263 (27, 240 €) per-patient in the intervention group versus CHF29, 477 (27, 439 €) in the control group resulting in per-patient cost savings of CHF214 (199 €). Per-patient cost savings was CHF19.56 (18.21 €) when also accounting for dietician costs (full cost analysis). These cost savings were mainly due to reduced ICU length of stay and fewer complications. We also calculated costs to prevent adverse outcomes, which were CHF276 (256 €) for one severe complication, CHF2, 675 (2490 €) for one day in ICU, and CHF7, 975 (7423 €) for one death. For the full cost analysis, these numbers were CHF872 (811 €), CHF8, 459 (7874 €) and CHF25, 219 (23, 475 €). Sensitivity analyses confirmed the original findings. Conclusions: Our evaluation demonstrates that in-hospital nutritional support for medical inpatients is a highly cost-effective intervention to reduce risks for ICU admissions and hospital-associated complications, while improving patient survival. The positive clinical and economic benefits of nutritional support in at-risk medical inpatients calls for comprehensive nutrition programs, including malnutrition screening, consultation, and nutritional support. Trial registration: ClinicalTrials.gov number, NCT02517476 .